Physical activity, time in front of the computer, sleep hours and body mass index in adolescents in times of pandemic - Flores Paredes, Alcides (2022)
The COVID-19 pandemic has resulted in enormous changes in people’s daily life activities. The levels of physical activity have decreased, time in front of the computer has increased, and this has caused physical inactivity and sedentary lifestyles in schoolchildren. The authors’ objective was to determine the direct relationship between physical activity, time in front of the computer and sleep hours, on the one hand, and, on the other, body mass index in adolescents of ages 12-17 in the region of Puno, Peru. The approach used is quantitative, and the type of research undertaken is non-experimental with a cross-cutting design. An intentional non-probabilistic sample was applied, consisting of 485 adolescents (241 females and 224 males) with an average age of (14.14 ± 1.34). The instruments used were the physical activity questionnaire, the time in front of the computer with Cronbach’s Alpha reliability analysis of .918 and .862, plus the self-report of body weight and standing height. Results: 20.65% of females show a low physical activity level, while high physical activity is predominant in 9.87% of males; 14.19% of females spend more time in front of the computer during the week (6-7 hours per day), in contrast with males (12.26%); 23.66% of females show overweight and 5.81% of them show obesity, while for males these percentages are 20% and 3.23%. An inversely proportional Spearman Rho correlation of -0.167 and p < .01 exists. The conclusion is that the body mass index increases with less physical activity.